Synchronizing noncontact rack-and-pinion devices - Nasiri, M; Miri, M; Golestanian, R (2012)
The lateral Casimir force is employed to propose a nanoscale mechanical device composed of one rack and N pinions. A coupling between the pinions via torsional springs is shown to coordinate their motion through a synchronization transition. The system can work against loads that are greater than the lateral Casimir force for each device. The existence of a stable synchronized state ensures that the system could operate in full coordination without the need of delicate fine tuning of all the characteristics such as the spring constants, the corrugation amplitudes, and the distances between the rack and the pinions. © 2012 American Institute of Physics.